ASUHAN KEBIDANAN PADA IBU C INPARTU KALA 1 FASE AKTIF DENGAN PENERAPAN GYM BALL UNTUK MENGURANGI NYERI PERSAlINAN DI TPMB DEWI SANDRA LUBIS KECAMATAN MEUREBO KABUPATEN ACEH BARAT TAHUN 2025 - Syafaiz, Cut Nabila Putri; Asmanidar, Asmanidar; Norisa, Nanda; Yushida, Yushida (SINERGI : Jurnal Riset Ilmiah, 2025)
Introduction: The 1st stage of active phase of labor lasts 7 hours. However, the length of the first stage of labor for each mother varies greatly, this is related to whether the contractions are good or not. Contractions that produce opening generally show increasingly frequent frequency and longer duration. The contractions that occur cause discomfort to the mother, namely pain. The Gym Ball is an alternative aid to speed up the progress of labor by widening the pelvic area. Purpose: research The purpose of this case study is to provide midwifery care for mother C at TPMB Dewi Sandra, West Aceh Regency with labor pain in the first stage. Research Method: The design of this care is in the form of a case study with a qualitative approach, the subject of this case study is mother C, 25 years old G1P0A0, 40 weeks gravida at TPMB Dewi Sandra in West Aceh Regency, this research was conducted on March 09 2025. Results Research: The results of midwifery care during the 1st stage show that the use of a gym ball can reduce the scale of pain felt by the mother, and can also reduce the duration of the 1st stage of the active phase in mothers who are about to give birth. Conclusion: gym ball can reduce pain and shorten the duration of the first stage of labor in C G1P0A0 mothers.